An approach to difficult airway in infants: Comparison of GlideScope® Spectrum LoPro, GlideScope® Spectrum Miller and conventional Macintosh and Miller blades in a simulated Pierre Robin sequence performed by 90 anesthesiologists - Irouschek, Andrea; Moritz, Andreas; Kremer, Sven; Fuchte, Tobias; Danzl, Anja; Schmidt, Joachim; Golditz, Tobias (PLoS ONE, 2023)
BACKGROUND: Airway management can be challenging in neonates and infants. The Pierre Robin sequence (PRS) is a condition characterized by micrognathia, glossoptosis and airway obstruction. The airway management of these patients poses great challenges for anesthesiologists and pediatricians alike. To date, there has been no direct comparison of the hyperangulated GlideScope® Spectrum LoPro (GLP), the straight GlideScope® Spectrum Miller (GSM), a conventional Macintosh (MC) and a conventional Miller blade (ML) in patients with PRS. METHODS: For this purpose, 90 anesthesiologists (43 with limited experience, 47 with extensive experience) performed orotracheal intubation on an Air-Sim® Pierre Robin X manikin using GLP, GSM, MC and ML in randomized order. 'Time-to-vocal-cords', 'time-to-intubate', 'time-to-ventilate', the severity of oral-soft-tissue-trauma and the subjective evaluation of each device were recorded. RESULTS: A significantly faster and better view of the vocal cords and lower oral-soft-tissue-trauma was achieved using the GLP (p<0.001). Though, there were no significant differences in the 'time-to-intubate' or 'time-to-ventilate'. The highest intubation success rate was found with GSM and the lowest with GLP (GSM 100%, ML 97.8%, MC 96.7%, GLP 93.3%). When using the videolaryngoscopes, there were no undetected esophageal intubations but in six cases prolonged attempts of intubation (>120s) with the GLP. In the sub-group with extensive experience, we found significantly shorter intubation times for the GSM and ML. The GLP was the tool of choice for most participants, while the conventional MC received the lowest rating. CONCLUSIONS: Videolaryngoscopy leads to increased safety for the prevention of undetected esophageal intubation in the airway management in a PRS manikin. Hyperangulated blades may ensure a good and fast view of the vocal cords and low oral-soft-tissue-trauma but pose a challenge during the placement of the tube. Specific skills and handling seem to be necessary to ensure a safe tube placement with this sort of blades.
CRIS-Team Scopus Importer:2023-08-11

Comparative study of the McGrath™ videolaryngoscope blades and conventional laryngoscopy efficacy during mechanical chest compressions: Insights from a randomized trial with 90 anesthesiologists on objective and subjective parameters - Golditz, Tobias; Schmidt, Joachim; Birkholz, Torsten; Danzl, Anja; Moritz, Andreas; Ackermann, Andreas; Irouschek, Andrea (PLoS ONE, 2024)
Aims This study aimed to compare the efficacy and utility of the McGrath™ videolaryngoscope, using the Macintosh-like McGrath™ MAC blade and the hyperangulated McGrath™ MAC Xblade with a conventional Macintosh blade under simulated resuscitation conditions. Methods A prospective, randomized study under conditions mimicking ongoing chest compressions was conducted with 90 anesthesiologists. Intubation success rates, time-to-vocal cords, time-to-intubate, and time-to-ventilate were measured. Additionally, the study assessed the subjective ratings and the perceived workload using the ‘NASA-task-load-index’ during the procedure. Results The overall intubation success rate was device dependent 99–100%. The McGrath™ MAC and McGrath™ MAC Xblade showed faster visualization times compared to conventional blades. The MAC blade demonstrated superior performance in time-to-intubate and time-to-ventilate compared to both conventional and MAC Xblades. Despite excellent visualization, the MAC Xblade posed challenges in tube placement, reflected in a prolonged intubation time of >120 seconds in one case. Both MAC and MAC Xblade reduced potential dental injuries and interruptions to chest compressions compared to conventional laryngoscopes. User experience significantly impacted intubation times with conventional laryngoscopes, but this effect was mitigated with videolaryngoscopy. Participants reported lower stress and effort when using videolaryngoscopes, with the MAC blade rated superior in perceived time pressure. Conclusion The study supports the superiority of videolaryngoscopy with a Macintosh-like blade over conventional laryngoscopy during mechanical chest compressions, particularly for less experienced users. The McGrath™ MAC blade, in particular, offers advantages in intubation time, user-friendliness, and reduced stress. However, the MAC Xblade’s challenges during tube placement highlight the need for further clinical validation. Continued research is essential to refine guidelines and improve resuscitation outcomes.
CRIS-Team Scopus Importer:2024-09-27

Managing One-Lung Ventilation in Tracheostomized Patients: A 6-Year Retrospective Analysis - Golditz, Tobias; Schmidt, Joachim; Ackermann, Andreas; Danzl, Anja; Birkholz, Torsten; Sirbu, Horia; Irouschek, Andrea (Thoracic and Cardiovascular Surgeon, 2024)
Background To ensure safe and optimal surgical conditions in thoracic surgery, one-lung ventilation is crucial. Various techniques exist to achieve one-lung ventilation. Tracheotomized patients who require one-lung ventilation represent a unique and rare subgroup that demands specialized knowledge and skills. The very limited literature has discussed alternative methods, no randomized controlled trials have addressed this issue yet. Methods We performed a retrospective analysis of patients who underwent one-lung ventilation in the Department of Thoracic Surgery of a German University Hospital between 2016 and 2021. The study assessed patient demographics, airway management techniques, ventilation parameters, and adverse events. Results In 3,197 anesthesia procedures during the observation period, 152 patients had an existing tracheostomy, of which 56 required one-lung ventilation. Among others in 42 cases, a tracheostomy tube was combined with a bronchial blocker, and in 10 cases, a double-lumen tracheostomy tube was used. There were no severe complications. Intraoperative dislocations that required repositioning of the device occurred in six patients (13.3%) with bronchial blockers and one patient with double-lumen tracheostomy tube (10%). Conclusion The management of one-lung ventilation in tracheotomized patients presents unique challenges. While double-lumen tracheostomy tubes have specific advantages, we recommend considering their use carefully. For most tracheotomized patients, bronchial blockers in conjunction with a tracheostomy tube are used, which offers safety and practicality, irrespective of the tracheostomy's age or type. Further research and randomized controlled trials are warranted to establish best practices for one-lung ventilation in this unique patient population.
CRIS-Team Scopus Importer:2024-05-03
Keywords: airway; anesthesia; guidelines; practice; trachea; ventilation